Improving Students’ Writing Ability of Descriptive Text Through Running Dictation Technique at The Eighth Grade of UPTD SMP Negeri 4 Gunungsitoli in 2022/2023 - Ainun Rahmin Zega; Hidayati Daeli; Hasrat S. Harefa; Kristof Martin E. Telaumbanua (Departement of Mathematics Education, 2023)
Writing is a important skill that needs to be mastered to develop their English in written media to convey their ideas. Writing is the process of expressing ideas thinking feelings in words on a piece of paper. In writing, students can represent thoughts or opinions in the form of written language. The aim of the research is to Improve Students' Writing Ability of Descriptive Text Through Running Dictation Technique at the Eighth Grade of UPTD SMP Negeri 4 Gunungsitoli, which the total numbers of the students was 29 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, evaluation sheet and field note. From the result of each Cycle, the researcher found that the students got an improvement in their writing through Running Dictation. In the second meeting of cycle II, the researcher obtained the improvement of students, who achieved the Minimum Competence Criterion (70).There were 10 (35%) students who got score among 85-100 classified as “Very Good Criteria”, 13 (44%) students got score among 75-84 classified as “Good Criteria”, 6 (21 %) students who got score among 60-74 classified as “Enough Criteria”, no one students who reached the “Less Criteria” and no one students who reached the “Fail ”Criteria. In Cycle II the highest mark was 92 and the lowest was 71 . Based on the result above the researcher concluded that Running Dictation technique could be done in teaching writing and could improve the students’ writing ability.